Infarto agudo al miocardio en octogenarios, caracterización y comparación con pacientes menores en 20 años de registro - Ugalde P., Héctor; Sanhueza F., Maria Ignacia; Yubini L., María Cecilia; Rozas A., Sebastián (Revista Hospital Clínico Universidad de Chile, 2016)
Introduction: cardiovascular diseases are the main cause of death in Chile, being acute myocardial infarction (AMI) the most frequent. Its incidence increases with age, so, as the population gets older; a higher number of cases is expected. Despite this, AMI within octogenarian patients (OP) has been understudied in our country and worldwide; there are no specific guidelines for their management, only a few isolated studies that reveal the poor applicability of the standard treatments indicated in AMI clinical guidelines. Objective: To describe the clinical features, initial treatment, in-hospital evolution and five-year outcome of OP with AMI, and compare them to patients under 80 years of age. Method: Consecutive registration of all patients diagnosed with AMI that were hospitalized in our coronary unit between 1988 and 2007. Description of clinical features, in-hospital and 5-year evolution of all OP cases. Comparison to the younger group of patients through chi-square or t-student tests, considering p-value <0.05 as statistically significant. Results: 1851 AMI patients were registered within this period, of which 135 (7,3%) were OP. The mean age was 83,7 years (80-100), 59% chronic hypertension, 22% diabetes, 11% smokers, 44% had history of angina and 13% previous AMI. The mean evolution time was 10 hours (80% <12 hours), 67% had ST- segment elevation (STE), 56% anterior-wall AMI. 29% underwent reperfusion therapy, and 64% presented AMI complications, mainly cardiac insufficiency. Coronarography was performed to 42% of OP, 33% were revascularized. In-hospital mortality was 29%, mainly because of cardiac insufficiency, 5-year mortality was 52.1%. Compared to younger patients, OP account for more female cases, higher Killip-scores, less STE-AMI, receive less reperfusion therapy and early beta-blockers, have more complications, are less studied and revascularized, and have higher mortality rates. Conclusion: OP have initial characteristics that configure greater severity to AMI. Besides, they are treated more conservatively, having a worse in-hospital evolution along with higher early and 5-year mortality. We suggest that this conservative behavior accounts for an important part of the unfavorable outcomes among OP, according to the few international studies available on this topic.